RANCANG BANGUN MODEL PENGENDALIAN DANA OPERASIONAL PENDIDIKAN (BOP) PENDIDIKAN ANAK USIA DINI (PAUD) DENGAN PENDEKATAN SOFT SYSTEM METHODOLOGY PADA DINAS PENDIDIKAN KABUPATEN LAMPUNG SELATAN - Agus Purnomo; Yeli Erika (Universitas Bandar Lampung (UBL), 2019)
Public problems are problems that concern the interests of many people which are very crucial to be handled by the government, so that they require serious and alternative handling to solve these public problems. One of the public problems that require serious handling is the problem of education. Every child has the right to education and teaching in the context of personal development and the level of intelligence according to their interests and talents. Early childhood education has an important meaning for the future of children in helping to apply good knowledge and discipline in early childhood, as well as assisting the development of children's character through the process of understanding children's character and social skills with their surroundings. To support the operational activities of education, the government provides Operational Assistance for the Implementation of Early Childhood Education which functions to improve quality education services.Based on the formulation of the problem above, the aim of this study is